Analisis Gaya Bahasa Pada Lirik Lagu Rossa Dalam Album Another Journey: The Beginning Dan Pemanfaatannya Sebagai Bahan Ajar Puisi Di SMA Kelas X - Aida, Nada Nur; Nurhasanah, Een; Suntoko, Suntoko (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to describe (1) the form of linguistic style in Rossa's song lyrics in the album Another Journey: The Beginning; (2) The research results are used as open material in class X high school. The theory that researchers use in this discussion is the theory of language styles according to Tarigan (2013). The subject of this research is the song lyrics on the album Another Journey: The Beginning. The researchers took the data for this research from Rossa's song lyrics on the album Another Journey: The Beginning, which consists of 10 songs. The method used in this research is descriptive analysis. The data collection techniques used were observation, close observation techniques and literature study. This research uses three stages of the data analysis process, namely data reduction, data presentation and conclusions. Based on the results of data analysis, there are 80 language styles in Rossa's song lyrics on the album Another Journey: The Beginning.